Report on the Implementation of Work Package 6 “Implementation of Methodology” in the Framework of the IRNet Project - Smyrnova-Trybulska, Eugenia; Malach, Josef; Kostolányová, Kateřina; Morze, Nataliia; Kommers, Piet; Noskova, Tatiana; Pinto, Paulo; Cubo Delgado, Sixto; Drlík, Martin; Issa, Tomayess; Romanyukha, Maryna (International Journal of Research in E-learning, 2017)
This article, prepared by an international team of researchers from different scientific areas connected with ICT, e-learning, pedagogy, and other related disciplines, focuses on the objectives and some results of the international project IRNet (www.irnet.us.edu.pl). In particular, the article describes research tools, methods, and a procedure of the Work Package 6 “Implementation of Methodology,” that is, objectives, tasks, deliverables, publications, and implementation of research trips in the context of the next stages and Work Packages of IRNet project – International Research Network.